African Union Handbook 2019 (African Union Commission and New Zealand Ministry of Foreign Affairs and Trade/Manatu Aorere Addis AbabaET, 2014)
This Handbook serves as a factual and concise reference guide to all aspects of the African Union and its Commission, and remains an invaluable tool for anyone working with, and within, the AU system.